IDENTIFYING BARRIERS AND TARGET COMPLIANCE FOR SELF-CARE IN TYPE 2 DIABETES PATIENTS - Elisângela da Cruz Vargas; Sumaya Giarola Cecilio; Célia Luciana Guedes Barbosa Brasil; Heloisa de Carvalho Torres (Universidade Federal do Paraná, 2015)
The objective was to identify barriers and compliance with targets for the development of self-care practices in chronic patients suffering from type 2 Diabetes Mellitus. Descriptive and exploratory study involving 30 users, undertaken through home visits at three primary health care services in Belo Horizonte, Minas Gerais in 2014. The barriers and targets cited were analyzed using relative frequencies and grouped into categories. 63.1% of the users presented difficulties related to psychosocial and cultural behaviors, 16.5% to environmental and structural behaviors, 3.3% economic behaviors, 6.6% related to other factors and 10% did not consider they had any relevant difficulties to take care of their health. Sixty percent of the users are capable of seeking solutions for the barriers and of making informed decisions that are appropriate to their health and life context, trying to find solutions to cope with barriers in diabetes self-care practices.